The Urgency of Establishing Compensation Standards and Minimum Wage Schemes for Interns from a Justice Perspective: A Normative Study on Internship Providers - Gutama, Alma Florydia; Sadiawati, Diani (Dinasti Research, 2025)
The lack of harmonization in regulations governing internship programs in Indonesia has led to ambiguity regarding the legal status of interns, resulting in weak legal protection and the absence of fair compensation standards, thereby potentially giving rise to disguised employment. Based on an analysis using the theories of justice of Gustav Radbruch, John Rawls, and the Critical Legal Studies (CLS) perspective, it was found that the existing regulations, namely Minister of Manpower Regulation No. 6 of 2020, Minister of Education, Culture, Research, and Technology Regulation No. 63 of 2024, and Minister of Manpower Regulation No. 8 of 2025, still overlap and have not established clear compensation standards. This situation contradicts the principles of justice as fairness and substantive justice because it disregards the economic rights of interns. Therefore, a Presidential Regulation (Perpres) is needed as a legal umbrella to unify inter-ministerial provisions and establish National Compensation Standards Based on the Minimum Wage (UMP), with a scheme of 25% of the UMP for curricular internships, 40% for non-curricular internships, and 50% for fresh graduates, in order to realize a fair, adaptive, and legally certain internship system.